Alnustone and Curcumin from Curcuma xanthorrhiza Roxb. as Potential Multi-Target Anti-Inflammatory Adjuvants in Pulpitis: An in silico Molecular Docking Study - Sandra, Ferry; Djamil, Melanie Sadono; Natassya, Priska; Endriyana, Jessica; Pratitis, Visi Endah (The Prodia Education and Research Institute (PERI), 2026)
BACKGROUND: Pulpitis is an inflammatory disorder of the dental pulp driven by activation of the toll-like receptor 4 (TLR4)/myeloid differentiation primary response 88 (MyD88)/interleukin-1 receptor-associated kinase 1 (IRAK-1)/tumor necrosis factor (TNF) receptor-associated factor 6 (TRAF6)/nuclear factor kappa B (NF-κB) signaling cascade and excessive production of pro-inflammatory cytokines. Bioactive compounds from Curcuma xanthorrhiza have demonstrated anti-inflammatory potential, but their molecular interactions with key proteins involved in pulpal inflammation remain unclear. This study aimed to evaluate the binding affinity and interaction profiles of major C. xanthorrhiza derived compounds with inflammation-related protein targets using an in silico molecular docking approach.METHODS: The active molecule (arcurcumae, germacrone, curcumin, xanthorrhizol, alnustone, and α-cedrene) were obtained from PubChem, while target proteins (TLR4, MyD88, IRAK-1, TRAF6, inhibitor of kappa B kinase (IKK), NF-κB, interleukin (IL)-1β, TNF-α, and IL-6) were retrieved from the protein data bank. Toxicity and physicochemical properties were predicted using ProTox-3.0 and SwissADME. Active molecule and protein preparation was performed using PyRx and BIOVIA Discovery Studio, respectively. The molecular docking was conducted with CB-Dock 2.0 employing AutoDock Vina.RESULTS: Alnustone and curcumin exhibited the strongest multi-target binding affinities toward several key proteins involved in the TLR4/MyD88/IRAK-1/TRAF6/IKK/NF-κB inflammatory signaling pathway. Alnustone demonstrated particularly strong interactions with TLR4 (-9.0 kcal/mol), IRAK-1 (-8.7 kcal/mol), NF-κB (-7.3 kcal/mol), TNF-α (-8.3 kcal/mol), and IL-6 (-6.1 kcal/mol), while curcumin showed high binding affinity to TRAF6 (-8.3 kcal/mol) and IL-1β (-8.6 kcal/mol). Interaction analyses indicated stable ligand–protein complexes supported by hydrogen bonding, hydrophobic interactions, and π-alkyl contacts within the active binding sites.CONCLUSION: Alnustone and curcumin displayed relatively strong multi-target binding to key proteins in the TLR4/MyD88/NF-κB pathway, supporting their possible potential as adjunctive anti-inflammatory agents for pulpitis and warranting further experimental validation.KEYWORDS: Curcuma xanthorrhiza, molecular docking, pulpitis, NF-κB, anti-inflammatory